Empowerment Bureaucratic equipment resources Regional autonomy in local government - Hartawan Hartawan (Indonesia Prime, 2018)
The publication of the acts is among those most valued as an indicator of the seriousness of the central government to respond to community aspirations and also to change the system of deluding government for some 32 years in a row A new order Pemetah that caused negative implications for the organization of the local governance system is decentralized. Also, there is the advent of a phenomenon threatening the disintegration of the nation that led to the secession of the State Union of the Republic of Indonesia, as we saw in various media. So want-not want the central government must meet regional autonomy requirements by putting them off